The Analysis of Role Teacher Personality Competence, Curriculum, and School Climate on Islamic Student’s Morals Amid the Covid-19 Pandemic - Ruslan Ruslan; Saparuddin Saparuddin; Muhammad Alqadri Burga (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The purpose of this study was to analyze the influence of teacher personality competencies, the curriculum, and the climate of Islamic boarding school on the morals of students in Sulawesi Selatan district, Indonesia. This type of research is a survey with a quantitative approach. Data collection methods using questionnaires, documentation, and observation. Data analysis using descriptive statistical and inferential statistical analysis techniques. The results showed that the teacher's personal competence, the curriculum, and climate of the Islamic boarding school have a positive and significant effect both partially and simultaneously on the morals of the students